تحليل التقابل بين اللغة الفصحى واللغة العامية المصرية من الناحية الصوتية في غناء عمرو دياب - Mamnunah Mamnunah (OKARA: Jurnal Bahasa dan Sastra, 2018)
Egyptian Arabic Âmiyah and Arabic Fushâ have similarities and differences in terms of consonant and vowel sound, the case of similarities and differences of those phonological aspects were found in Amr Diab’s song. This research is intended to know the similarities and the differences of consonant and vowel sounds between Egyptian Arabic Âmiyah and Fushâ in Amr Diab’s songs. The contrastive analysis was utilized to identify the differences and the similarities of both languages in the subject. The results revealed the similarities of consonant sounds between Egyptian Arabic Âmiyah and Arabic Fushâ found in the consonants of أ، ب، ت، ح، خ، د، ر، ز، س، ش، ص، ع، غ، ف، ك، ل، م، ن، و، ه، ي, while the differences are in the consonant sounds of ذ which is pronounced as د\ز, then ض pronounced with D, ط sounds like T, ظ sounds like Z, and ق sound the same as أ. Then, the similarities in vowel sounds between Arabic Fushâ and Egyptians Arabic Âmiyah are sounds of fathah, dhommah, kasrah thowilah {long} and fathah, dhommah, kasrah qashirah {short}, and the differences of vowel sounds are between the sounds of fathah and kasrah ê also vowel of fathah and dhommah ô.